Gender learning in Alice Munro’s short story entitled “Boys and Girls” - Asmarani, Ratna (Universitas Muhammadiyah Sidoarjo, 2023)
The issues around gender is inexhaustible since gender can be analyzed from many perspectives. The focus of this paper is to discuss the gender learning experienced by the young girl in a short story entitled “Boys and Girls” written by Alice Munro. The discussion includes the young girl’s gender defiance, gender learning, and gender acceptance. To support the discussion several issues around gender are reviewed. Besides a comprehensive definition of gender, issues concerning doing gender, gender identity, gender order, gender segregation, gender learning, gender presentation, gender display, and others are reviewed. The analysis is also combined with the conversation analysis by considering the influence of the language that leads to gender learning of the female character in the short story. The methods used are a combination of library research method with its close reading, qualitative method, and contextual method. The result shows that gender learning is inevitable especially in an isolated place. Although the young girl tries to defy the gender learning she finally has to accept it. This situation correlates with Simone de Beauvoir’s statement “ONE is not born, but rather becomes, a woman” (De Beauvoir, 1956: 273) in her phenomenal book The Second Sex. Thus, the short story implies that being a girl in a strict male context is not easy, she has to surrender to the gender roles that are constructed for her, and the chances to actualize herself is limited or even non-existent. HIGHLIGHTS: Gender construction is spread naturally through many ways, such as gender identity, gender order, gender display, or gender learning. The spread of gender construction can be done through daily examples or through language learning. Whatever gender defiance is carried out to escape from the gender construction, in the end, incessant gender learning results in gender acceptance.